Testing the inadvertency hypothesis: Incidental news exposure and political disagreement across media platforms. (August 2020) - Barnidge, Matthew
The inadvertency hypothesis predicts that people encounter political difference in social media spaces not by design, but rather as a by-product of social media's affordances and cultural logics. The hypothesis implies that incidental news exposure plays a central role in starting conversations from which perceived political disagreement may arise. Relying on a two-wave, online survey collected before and after the 2018 US Midterm Elections (N = 1493), this study builds on prior tests of the inadvertency hypothesis. It also elaborates on the hypothesis by comparing social media platforms. Results are supportive of the inadvertency hypothesis, more so for social networking sites such as Facebook than for other types of social media. Results are discussed in light of the study's contribution to literature on social media and democracy.